Early diagnosis of post-varicella necrotising fasciitis: A medical and surgical emergency - Rose Xavier; Bobby Abraham; Vinod Jacob Cherian; Jobin I Joseph (Wolters Kluwer Medknow Publications, 2016)
Necrotising fasciitis (NF) is an extremely rare complication of a rather common paediatric viral exanthem varicella. Delayed diagnosis and treatment can lead to significant morbidity and mortality. Laboratory risk indicator of NF score aids in early clinical diagnosis in suspected cases of post-varicella NF thus enabling timely intervention. Surgery delayed for more than 24 hours, is an independent risk factor for death. Surgical debridement with good antibiotic coverage is the definitive treatment for NF.